Penetapan Ekstrakurikuler Wajib untuk Siswa Sekolah Menengah Atas Berdasarkan Kecerdasan Majemuk - Muggy David Cristian Ginzel; Asep Saefuddin; Erfiani Erfiani (Department of Statistics, IPB, 2020)
Senior high school in Indonesia is divided into two groups, namely Natural science and Social science. Those grouping of majors is allegedly not appropriate enough the potential of students yet because of the multiple intelligence of each student is different. This study aims to establish an extracurricular program for everyone grouped by multiple intelligences carried out by each student. The method used in this study are the non-hierarchical clustering k-Means and hierarchical clustering Ward method. The k-Means method used to determine the effective number of groups, while Ward method used to identify the member of each cluster and the recommendation of extracurricular in the cluster obtained. Based on the results of the clustering analysis, there are five clusters obtained, Language and Fine Arts; Communication; Leadership; Nature Lovers; and also Design and Photography.